2017
DOI: 10.1007/s13246-017-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of treatment delivery uncertainties on treatment effectiveness for lung SABR

Abstract: To quantify the impact of treatment delivery uncertainties on lung stereotactic ablative body radiotherapy (SABR) plans for step-and-shoot intensity-modulated radiotherapy (ssIMRT) and volumetric modulated arc therapy (VMAT). Baseline ssIMRT and VMAT treatment plans were generated for a cohort of 18 lung SABR patients. Modified plans were generated for each baseline plan by systematically varying gantry and collimator angles between - 5 and + 5 degrees, as well as multi-leaf collimator (MLC) leaf position erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Sen et al 21 reported that when the magnitude of MLC random error in nasopharyngeal carcinoma reaches 2 mm, it has few effects on target and OARs. Blake et al 22 reported that there was less patient‐to‐patient variation occurred from MLC delivery uncertainties in VMAT than step‐and‐shoot IMRT. The abovementioned studies on MLC position error were all based on the manual planning.…”
Section: Discussionmentioning
confidence: 99%
“…Sen et al 21 reported that when the magnitude of MLC random error in nasopharyngeal carcinoma reaches 2 mm, it has few effects on target and OARs. Blake et al 22 reported that there was less patient‐to‐patient variation occurred from MLC delivery uncertainties in VMAT than step‐and‐shoot IMRT. The abovementioned studies on MLC position error were all based on the manual planning.…”
Section: Discussionmentioning
confidence: 99%
“…15 baseline lung SBRT VMAT plans (15 patients) and 88 generated plans with different delivery variations across these patients were selected from a previous planning study, 19 based on the clinical significance of the differences. The plans were generated in the Pinnacle (Phillips Healthcare, Fitchburg, WI, USA), v9.8 treatment planning system (TPS), using a 6 MV photon beam from an Elekta Versa HD linear accelerator with a 40 leaf pairs Agility MLC (Elekta, Crawley, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Any of these variations which caused any one or more of a range of DVH metrics to deviate by more than ±2% were defined as clinically significant. The following DVH metrics were considered; PTV (D mean , D max , V95%, V100%), spinal cord (D mean , D0.1 cc), and healthy lung (lung‐PTV) (D mean , V20 Gy) 19 . Only brief details were provided here of the planning study, to indicate the source of the selected plans, but full details can be seen in that reference 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this work was to investigate any variations in the ability of three dosimetry systems (ArcCHECK (3D), EPID (2D) and MatriXX Evolution (2D)) to detect systematic delivery errors in step-and-shoot IMRT. This work is part of a larger investigation by the local research group of the impact of uncertainties on advanced radiotherapy treatment techniques [18,[37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%